FAKTOR MANUSIA YANG BERHUBUNGAN DENGAN KEJADIAN KECELAKAAN KERJA PADA PETUGAS PEMADAM KEBAKARAN DI BPBD KOTA DENPASAR - Damayanti, Ni Kadek Krisna; Ani, Luh Seri (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025, 2025)
ABSTRACT Workers have a high risk of occupational accidents because they are directly dealing with fire and other potential hazards. According to Heinrich, 80% of accidents are caused by unsafe actions. There were 23,825 cases of firefighter’s injury in 2019 in America. 63.3% of Majalengka Regency firefighters had work accidents in 2021 and 62.7% of Medan City firefighters had work accidents in 2022. The purpose of this study was to determine the human factors associated with work accidents in firefighters. This study is a quantitative study with a cross sectional approach. The sample in the study was 80 people and were selected using simple random sampling technique. Data analysis was carried out univariate and bivariate. The results of the chi square test there was a significant relationship between age (p = 0.020), OHS knowledge (p = 0.026), work attitude (p = 0.048), and the use of PPE (p = 0.034) with work accidents. There is no significant relationship between length of service (p = 0.669) and level of education (p = 0.196) with work accidents. The Denpasar City Regional Disaster Management Agency is expected to provide standardized PPE and take a persuasive approach to increase firefighter’s awareness of using PPE. Keywords: Occupational accidents, Firefighters, Human factors